Analysis of The Influence of Transformational Leadership and Organizational Culture on The Performance of Civil Servants Through Public Innovation in The Pamekasan Regency Government - Wijaya, Dennie Surya; Triatmanto, Boge; Arifin, Syaiful (Proceedings of International Conference of Graduate School on Sustainability, 2026)
This study aims to analyze the influence of transformational leadership and organizational culture on the performance of Civil Servants (PNS), both directly and indirectly through public innovation in the Pamekasan Regency Government. The research method used is quantitative with a survey approach. Data were collected through questionnaires from 126 Civil Servants, who served as respondents, and analyzed using Structural Equation Modeling (SEM) with AMOS. The results prove that: (1) Transformational leadership and organizational culture have a direct positive and significant effect on Civil Servant performance; (2) Transformational leadership and organizational culture have a direct positive and significant effect on public innovation; (3) Public innovation has a direct positive and significant effect on Civil Servant performance; and (4) Public innovation partially mediates the relationship between transformational leadership and organizational culture with Civil Servant performance. The conclusion of this research affirms that to improve Civil Servant performance, the Pamekasan Regency Government needs to strengthen the application of transformational leadership, build a conducive organizational culture, and actively encourage public innovation. Public innovation serves as a strategic mechanism that translates leadership values and organizational culture into tangible performance improvements.